2022
DOI: 10.3390/cancers14040959
|View full text |Cite
|
Sign up to set email alerts
|

Radioembolization of Hepatocellular Carcinoma with 90Y Glass Microspheres: No Advantage of Voxel Dosimetry with Respect to Mean Dose in Dose–Response Analysis with Two Radiological Methods

Abstract: In this confirmatory study, we tested if a calculation that included the non-uniformity of dose deposition through a voxel-based dosimetric variable Ψ was able to improve the dose–response agreement with respect to the mean absorbed dose D. We performed dosimetry with 99mTc-MAA SPECT/CT and 90Y-PET/CT in 86 patients treated 8 instead of 4 days after the reference date with 2.8 times more 90Y glass microspheres/GBq than in our previous study. The lesion-by-lesion response was assessed with the mRECIST method an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…There are also some studies showing a signi cant correlation between absorbed dose metrics calculated from 90 Y-bSPECT and 90 Y-PET images (46), paving the way for the use of 90 Y-bSPECT to establish a robust dose-response relationship. On the other hand, the use of voxel-dosimetry also remains a subject of discussion, as some authors demonstrate its validity in TARE (32), while others (5) show that it does not improve over MIRD approaches. those used in this study, showed equivalent signal-to-background ratios (50).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also some studies showing a signi cant correlation between absorbed dose metrics calculated from 90 Y-bSPECT and 90 Y-PET images (46), paving the way for the use of 90 Y-bSPECT to establish a robust dose-response relationship. On the other hand, the use of voxel-dosimetry also remains a subject of discussion, as some authors demonstrate its validity in TARE (32), while others (5) show that it does not improve over MIRD approaches. those used in this study, showed equivalent signal-to-background ratios (50).…”
Section: Discussionmentioning
confidence: 99%
“…As recommended (34) we avoided using threshold-based tumor segmentation on SPECT images as it often does not represent true anatomical extent due to heterogeneous microsphere distribution. In large lesions with a visible necrotic core in CT, the core was excluded from the lesion volume (5). Small tumors with a volume under 4 ml, considered equivalent of a 2-cm-diameter spherical lesions, were excluded from the analysis, as recommended (27,35).…”
Section: Work Ow Image Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue has been empirically solved in several studies by fitting together N and α in Eq. 6 , which resulted in tenfold lower radiosensitivity and unrealistic tumor cells number ranging from 0.4 [ 33 ] to 3.4 [ 4 , 34 ]. In fact, using the tumor cell number corresponding to the mean tumor volume (36 ml) and a standard deviation of 30% around the in vivo HCC cell radiosensitivity between patients is sufficient to rightly predict the observed TCP shape (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two dosimetric factors predict SIRT efficacy: a high tumor absorbed dose and homogeneous distribution of the microspheres in the tumor [ 3 , 11 , 56 ]. The tumor response rate will proportionally increase with the absorbed dose, reaching a plateau of complete response for the highest doses [ 50 , 55 , 56 , 57 , 58 ]. From a dosimetric point of view, the main limitation of SIRT effectiveness is the heterogeneity of the microsphere distribution in the tumor [ 3 ].…”
Section: Dosimetry Considerations Using Maa Spect/ctmentioning
confidence: 99%